Effect of land use change on water balance and suspended sediment yield of Taleghan catchment, Iran - Hosseini, Majid (2010)
The effects of global warming, climate change, and land use changes on catchment water balance and water quality have become the main concern in catchment water management in recent years. Due to rapid population growth upon dam construction, the Taleghan catchment in Iran has undergone rapid land use changes, urbanization, and water resource development for agriculture, industry, and domestic water supply. These changes could potentially cause devastating effects on both water balance and water quality in the catchment. However, there is no known study being conducted to predict the effect of land use changes on water balance and water quality in this area. Therefore there is a need for a physically-based and computationally efficient distributed hydrological model with a simple GIS interface to evaluate the effects of land use changes in Taleghan catchment. The main objective of this research was to examine the effect of land use changes on water balance and suspended sediment yield of the Taleghan catchment in northwest Iran. From a review of various models, a semi-distributed model, Soil and Water Assessment Tools (SWAT) was selected for this study. The model was applied to the study area and its performance for predicting runoff was evaluated. Two popular programs that are linked into SWAT namely SUFI2 and ParaSol were applied for calibration and validation purposes, respectively. Comparing the water balance between Joestan (upper part) and Galinak (outlet) stations showed evapotranspiration losses were around 38% and 49% of the precipitation, respectively. Surface runoff was 21% of the precipitation for the upper part of the catchment and 33% at the outlet. Groundwater and lateral flows took place mostly in the mountainous upper part of the catchment. The results of annual suspended sediment yield showed that more sedimentation took place upstream of Galinak with 7.3 t/ha but 5.8 t/ha at Joestan. The water balance at the outlet was predicted for the period between January 1995 and August 2004. The results shows 2.4% increase in surface runoff and 2.04% decrease of interflows. These results indicate the sediment yield increased from 7.3 t/ha to 8.3 t/ha at the outlet during the study period with progressively ascending surface runoff and suspended sediment yield and progressively descending interflows. Sediment yield predictions were compared to the seven land use scenarios. The maximum increase in sediment yields compared to the last observed land use (2007) was 1.6 t/ha (19%) for scenario 7 (all rangeland is bare). Scenario 2 (rangeland to agriculture, 0-20%) and scenario 6 (rangeland to the bare, 0-40%) showed increase of 4% and 12%, respectively. Scenario3 (agriculture to urban 0-20% slope), scenario 4 (agriculture to the urban, 0-40% slope), and scenario 5 (rangeland to the urban, 0-20% slope) showed decreases in sediment yields of 2.5%, 5.7% and 1.2%, respectively. The land use changes in the seven scenarios had varying effects on the water components in relation to slope steepness. These land use scenarios showed increase of 4%, 5.2%, 7.5%, 8%, 10%, and 15% in surface runoff and decrease of 8.7%, 10%, 12.7%, 30%, 31%, and 45% in groundwater flow for scenarios 2, 3,4,5,6, and 7, respectively. This research has successfully developed a customized SWAT model useful for water engineers and managers in their planning of future land developments of the Taleghan catchment. The database system of the Taleghan catchment, using dispersed datasets in GIS environment could be used not only for modeling purposes but also for decision making. The information on soil erosion sensitivity of a particular area in the catchment will be useful for the government planning of soil and water conservation control measure, such that priority actions on sediment control and restoration budget will be allocated where it is most required. The study has produced a technique with reliable capability and high accuracy for annual and monthly water balance components and suspended sediment yield over different slope classes of the Taleghan catchment. This can pave the way for similar studies in other catchments with the same climatic conditions.